Novel Linalool-Silver nanoparticles: Synthesis, characterization, and dual approach evaluation via computational docking and antibacterial assays - Hina Manzoor; Mohammad A. Alfhili; Shakeel Waqqar; Malik Arslan Ali; Faiza Hassan; Samiullah Khan; Muhammad Umer Khan (PLoS ONE, 2025)
In recent years, scientists have developed new medical delivery techniques based on nanotechnology and have been actively creating nanoparticles combined with various extracts from natural plant products. This study aimed to conjugate linalool surface with silver nanoparticles, investigate its characteristics, and evaluate its effectiveness as a possible new therapeutic target against bacterial strains. A CMC-linalool solution was used to create linalool-based AgNPs (LN@AgNPs), which were then characterized by UV-Vis, FTIR, SEM, DLS, and zeta potential studies. The shape, hydrodynamic diameter, and negative zeta potential were among the advantageous properties of the resultant particles, which improved their performance and stability. Antibacterial potential was assessed using both in silico and in vitro methods. According to molecular docking, LN@AgNPs exhibit strong interactions via hydrogen bonding and potential metallic chelation with important bacterial protein residues (Cys, His, and Thr). According to the in vitro assays, LN@AgNPs exhibited inhibitory zones comparable to those of azithromycin and stronger antibacterial efficacy than free linalool against Salmonella enterica , Bacillus subtilis , and Escherichia coli . According to these results, LN@AgNPs may be a good option for creating potent antimicrobial agents. To improve its therapeutic application, further investigation of its mode of action and in vivo safety profile is necessary.